2020
DOI: 10.4103/psychiatry.indianjpsychiatry_91_20
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-based classification of schizophrenia: A high density electroencephalographic and support vector machine study

Abstract: Background: Interview-based schizophrenia (SCZ) diagnostic methods are not completely valid. Moreover, SCZ-the disease entity is very heterogeneous. Supervised-Machine-Learning (sML) application of Artificial-Intelligence holds a tremendous promise in solving these issues. Aims: To sML-based discriminating validity of resting-state electroencephalographic (EEG) quantitative features in classifying SCZ from healthy and, positive (PS) and negative symptom (NS) subgroups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Considering research reproducibility, we utilized all but some of the epochs, which consist of the remaining epochs after the epochs containing artefact were removed in the preprocessing step. Next, we applied feature selection methods to conventional EEG features introduced in a previous study [7][8][9][10][11][12][13][14][15][16][17][18][19][20] to compare classification performances. The method would prevent classification performance of conventional EEG features from being underestimated in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering research reproducibility, we utilized all but some of the epochs, which consist of the remaining epochs after the epochs containing artefact were removed in the preprocessing step. Next, we applied feature selection methods to conventional EEG features introduced in a previous study [7][8][9][10][11][12][13][14][15][16][17][18][19][20] to compare classification performances. The method would prevent classification performance of conventional EEG features from being underestimated in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Johannesen et al used frequency domain features in the working memory task to differentiate between patients with schizophrenia and healthy controls [12]. Schizophrenia classification was also performed using statistical features including mean, skewness, and kurtosis [13,14]. It has been reported that the statistical descriptor of the variability within the EEG signal, the entropy measure and the fractal dimension related with it, are useful for schizophrenia classification [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…clustering coefficient in the right temporal region (T6) in the range of EEG theta rhythms (from 4 to 8 Hz) and concentration of Ruminococcus in microbiota; degree centrality in the range of beta-2 rhythms (from 20 to 30 Hz) in the right frontal area (Fp2) and white blood cell count; degree centrality in the range of beta-2 rhythms (from 20 to 30 Hz) in the right occipital area (O2) and neutrophil to lymphocyte ratio. Tikka et al [102] used high-resolution EEG (256 channels) isolating from it other features: maximum and minimum amplitude of spectrum power peaks in delta (0−4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and gamma (32-64 Hz) ranges, and performing wavelet analysis in these rhythm ranges. The following regions of interest were selected: projection on the cortex of the left inferior frontal gyrus, dorsolateral prefrontal cortex (DLPFC) of the inferior parietal lobe (IPL), and superior temporal gyrus (STG).…”
Section: Vázquez Et Almentioning
confidence: 99%
“…Within this context, there have also been recently developed artificial intelligence (AI)- and machine learning (ML)-based approaches, which promise an interesting implementation of statistical tools to build more accurate and precise predictive models of schizophrenia onset, illness course, and potential therapeutic outcomes [ 28 ]. These can also identify candidate variables that are putative to be characteristics of schizophrenia spectrum disorders, by allowing a personalized diagnosis, such as a set of resting-state electroencephalographic (EEG) quantitative features, and magnetic resonance imaging of structural and functional anomalies, and so forth [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%